Novel active-feedback device improves sleep quality in insomnia disorder: a randomized placebo-controlled trial - Ypsilanti, Antonia; van de Werken, Maan; Robson, Anna; Examilioti, Petra; Lazuras, Lambros (Frontiers in Sleep, 2025)
ObjectivesInsomnia disorder is a public health challenge associated with impaired cognitive functioning, reduced quality of life, and adverse mental health outcomes. This study examined the effectiveness of SleepCogni, an active-feedback device, in reducing insomnia symptom severity and improving perceived sleep quality in individuals with insomnia disorder.MethodA two-arm, parallel-group trial design was used, with 80 participants randomized to either the experimental group or the placebo control group. Participants provided self-reported measures of insomnia severity, sleep continuity, and user experience as main outcome variables.ResultsRepeated measures analysis of variance showed that participants in the experimental group reported significantly greater improvements in insomnia symptom severity than the control group (Time × Treatment). Although the mean difference did not reach the threshold for clinical significance, 37.5% of the participants achieved this threshold within 1 week of treatment. Mixed-effects models showed significant improvements in sleep efficiency and total sleep time, based on sleep diary records. Finally, an independent samples t-test and content analysis indicated a more positive user experience in the experimental group.ConclusionThe SleepCogni device appears to be a useful tool for improving sleep outcomes in individuals with insomnia disorder, showing effects on both insomnia severity and subjectively evaluated sleep. The SleepCogni device presents a useful intervention that might be used alone or as a complement to increase the effectiveness of existing treatments, such as cognitive behavioral therapy for insomnia.Clinical trial registrationhttps://osf.io/rswcb, identifier: osf-registrations-rswcb-v1.